An allelic variant of the PmrB sensor kinase responsible for colistin resistance in an Escherichia coli strain of clinical origin - Antonio Cannatelli (Nature Portfolio, 2017)
Abstract We investigated the colistin resistance mechanism in an Escherichia coli strain (LC711/14) isolated in Italy in 2014, from an urinary tract infection, which was previously shown to express a colistin resistance mechanism different from mcr-1. LC711/14 was found to carry a novel mutation in the pmrB gene, resulting in a leucine to proline amino acid substitution at position 10 of the PmrB sensor kinase component of the PmrAB signal transduction system. The role of this substitution in colistin resistance was documented by expression of the wild-type and mutated alleles in a pmrB deletion derivative of the E. coli reference strain MG1655, in which expression of the mutated allele conferred colistin resistance and upregulation of the endogenous pmrHFIJKLM lipid A modification system. Complementation of LC711/14 with the wild-type pmrB allele restored colistin susceptibility and decreased expression of pmrHFIJKLM, confirming the role of this PmrB mutation. Substitution of leucine at position 10 of PmrB with other amino acids (glycine and glutamine) resulted in loss of function, underscoring a key role of this residue which is located in the cytoplasmic secretion domain of the protein. This work demonstrated that mutation in this domain of the PmrB sensor kinase can be responsible for acquired colistin resistance in E. coli strains of clinical origin.